The hidden vulnerabilities behind financial sustainability: a case study of a sugarcane farm business in Pemalang City, Central Java, Indonesia (Sustainability in Debate, 2023)
This study assesses the financial viability of a 4-hectare sugarcane farming enterprise operated by Perhutani, an Indonesian State-Owned Enterprise. The farm is situated in the geographical limits of Pemalang City, which is located in the Central Java Province of Indonesia. This study employs a financial feasibility analysis approach that involves the computation of key financial indicators such as Net Present Value (NPV), Internal Rate of Return (IRR), Pay Back Period (PBP), Benefit Cost Ratio (BCR), and the application of sensitivity analysis. Overall, the assessment of the viability of a 4-hectare sugarcane farming enterprise indicates that it is financially feasible and has the potential to operate as a sustainable business. This conclusion is drawn from the positive numerical values obtained through various financial analysis techniques. Nevertheless, it is evident from the conducted sensitivity analysis that sugarcane farming is a highly susceptible business to fluctuations in prevailing conditions. When molasses production experienced reductions of 10% and 15%, most financial feasibility analysis estimates yielded negative values. The issue of production vulnerability extending beyond economic feasibility has been rendered inconspicuous by many reasons, including climate change.